The making of an Islamist public sphere in Bangladesh. Issue 4 (December 2019) - Rahman, Md Mizanur
The article examines the process of making an Islamist public sphere in Bangladesh and identifies the actors involved. It argues that Islamist social Islamization movements in the form of various da'wa (preaching) activities, madrassah activisms, and Islamist political parties' Islamization projects collectively contribute to the making of an Islamist public sphere. It shows how da'wa movements' everyday living experiences, madrassah's absolute authority over public Islam, and Islamist political parties' social welfare, and associated activities construct an Islamist imagination. A parallel counter Islamist discursive arena with secular discourse is in construction and circulation that formulates oppositional interpretations based on Islamist identities, interests, and needs. The article argues that instead of explicitly challenging the secular hegemonic discourse, Islamist social movements engage in a contested relationship with it, and gradually claim their separate position. It further maintains that although these Islamist movements differ ideologically, and vary the ways they perform and propagate Islam, they invariably contribute to the rise of an Islamist public sphere in Bangladesh.